2011
DOI: 10.1200/jco.2010.33.3922
|View full text |Cite
|
Sign up to set email alerts
|

Compendium of Unpublished Phase III Trials in Oncology: Characteristics and Impact on Clinical Practice

Abstract: A substantial number of cancer clinical trials with potential influence on clinical practice remain unpublished and many other trials are published after a substantial delay. Nonpublication of clinical trials breaks an implicit contract with participants, institutional review boards, and sponsors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 15 publications
3
17
1
1
Order By: Relevance
“…We found that the clinical trial data from 75% of abstracts reporting randomized trials and from 54% of those describing nonrandomized trials were published by March 2015, a statistically significant difference (p , .001). Our 75% rate of publication for abstracts reporting randomized trials in the ASCO database from 2009-2011 is similar to the 56%-91% reported by others who assessed rates of publication of randomized or large trials [1,9,[22][23][24][25][26][27]. Our finding that clinical data from only 54% of abstracts reporting on nonrandomized trials had been published 4-6 years after their ASCO submissions is consistent with the 56%-74% reported by others 5-7.5 years after publication of the abstract [9,10].…”
Section: Discussionsupporting
confidence: 81%
“…We found that the clinical trial data from 75% of abstracts reporting randomized trials and from 54% of those describing nonrandomized trials were published by March 2015, a statistically significant difference (p , .001). Our 75% rate of publication for abstracts reporting randomized trials in the ASCO database from 2009-2011 is similar to the 56%-91% reported by others who assessed rates of publication of randomized or large trials [1,9,[22][23][24][25][26][27]. Our finding that clinical data from only 54% of abstracts reporting on nonrandomized trials had been published 4-6 years after their ASCO submissions is consistent with the 56%-74% reported by others 5-7.5 years after publication of the abstract [9,10].…”
Section: Discussionsupporting
confidence: 81%
“…Within this cohort, older protocols were more commonly conducted in the adjuvant/curative setting and had longer accrual time. Furthermore, despite prior reports of an association between failure to meet primary endpoints and delay in publication [16], in our cohort, no temporal relationship was observed with the probability of a positive trial. Finally, it is also possible that protocols with more recent dates reflect updated version dates as opposed to original protocol dates.…”
Section: Discussioncontrasting
confidence: 99%
“…For the remaining 24 reports the weighted mean proportion of abstracts published was 55.9% (95% CI, 54.8% to 56.9%). The proportion of abstracts published for the 7 reports that only included abstracts of clinical trials [3, 11, 18, 21, 23, 28, 32] was 73.0% (95%CI, 71.2% to 74.7%).…”
Section: Resultsmentioning
confidence: 99%